A method for assessing measurement precision and stability of optical probes - Norman, James; Tonnellier, Xavier; Morantz, Paul (European Society for Precision Engineering and Nanotechnology, 2016)
The current strategy for measuring non-specular metre-scale surfaces – for instance segmented freeform optics post-grinding – in the mid- frequency bandwidths (S-filter), involves the use of contact probe based systems where measurement precision is a limiting factor. Equivalent non-contact optical probes claim accuracies up to an order of magnitude higher and could therefore improve current measurement systems. Chromatic confocal probes measure the distance to a surface using the principle of axial chromatic dispersion. The stability of a CHRocodile SE 300 μm probe was shown to be 200 ± 20 nm over an eight hour measurement period. A probe holder should be designed with a low thermal expansion material in order to thermally insulate the probe measurement for further investigation. The accuracy of the probe was assessed at the extremes of its measurement range. The maximum deviation over a 5 μm displacement was measured to be 85 nm. The entire measuring range should be investigated.
Keywords: Metrology; Non-specular surfaces; Non-contact probing; Long term stability